A Group Randomized Trial of School-Based Teen Courts to Address the School to Prison Pipeline, Reduce Aggression and Violence, and Enhance School Safety in Middle and High School Students. (1st October 2020) - Smokowski, Paul R.; Evans, Caroline B.R.; Rose, Roderick; Bacallao, Martica
ABSTRACT: This study evaluated the efficacy of School-Based Teen Courts (SBTCs) using a rigorous experimental trial with 24 middle- and high-schools randomly selected to receive SBTCs ( n = 12) or to business-as-usual without any SBTC program ( n = 12). Analyses examined school-level longitudinal growth models and individual-level pretest-posttest comparisons on school climate, student problems, and suspension rates. Longitudinal growth models revealed that SBTCs were significantly associated with positive changes in school satisfaction and reductions in delinquent friends for high school students, but showed no significant changes on other outcomes. Short-term suspensions decreased more than twice as much in SBTC schools versus comparison schools. There was a 47% reduction in bullying victimization in SBTC schools relative to a 22% reduction in comparison schools. These findings suggest that SBTCs have the potential to positively impact youth development.